The influence of oxytocin-based interventions on sleep-wake and sleep-related behaviour and neurobiology: A systematic review of preclinical and clinical studies. (December 2021) - Raymond, Joel S.; Rehn, Simone; Hoyos, Camilla M.; Bowen, Michael T.
Highlights: Oxytocin (OXT) interventions can influence sleep-wake behaviour and neurobiology. Preclinically, OXT system activation exerts wake-promoting effects at higher doses. Clinically, OXT seems to exert no or minor sleep-promoting effects at doses tested. Abstract: The oxytocin (OXT) system has garnered considerable interest due to its influence on diverse behaviours. However, scant research has considered the influence of oxytocin on sleep-wake and sleep-related behaviour and neurobiology. Consequently, the objective of this systematic review was to assess the extant preclinical and clinical evidence for the influence of oxytocin-based interventions on sleep-wake outcomes. The primary search was conducted on 22/7/2020 using six electronic databases; 30 studies (19 preclinical, 11 clinical) were included based on inclusion criteria. Studies were evaluated for risk of bias using the SYRCLE tool and the Cochrane risk of bias tools for preclinical and clinical studies, respectively. Results indicated manipulation of the OXT system can influence sleep-wake outcomes. Preclinical evidence suggests a wake-promoting influence of OXT system activation whereas the clinical evidence suggests little or no sleep-promoting influence of OXT. OXT dose was identified as a likely modulatory factor of OXT-induced effects on sleep-wake behaviour. Future studies are necessary to validate and strengthen these tentative conclusions about the influence of OXT on sleep-wake behaviour.